Sustained release solid dispersion of Metoclopramide HCL: formulation, evaluation and pharmacokinetic studies - S. L. Neha, Neelam Singh, Mohd Yasir (Journal of Applied Pharmaceutical Science, 2015)
In recent years oral controlled delivery systems have gained increased importance and interest since it is necessary to improve the systemic absorption of the drugs and patient compliance. In addition, controlled delivery systems maintain uniform drug levels, reduce dose and hence dose related side effect, and increase the safety margin. The objective of present work was prepared sustained release solid dispersion of Metoclopramide HCl by solvent evaporation method. Several polymers like combination of Eudragit RSPO - Eudragit RLPO and Guargum-Egg albumin as synthetic and natural polymers respectively were used. Several parameters like Solubility, Partition coefficient, Drug content, Percent drug release, Bulk density, Tapped density and Carr’s index were evaluated and all parameters were found to be in acceptable range. The results of XRD and SEM analysis were showed that the drug was converted into a solid dispersion. The In vivo studies were performed on Albino Wistar rats and various pharmacokinetics parameters were determined. The whole study was showed that the solid dispersion of Metoclopramide HCl sustained the release rate of drug for a prolong period of time at least 12 hrs and shows to increase the bioavailability and simultaneously decrease the dosing interval as well as dosing amount. The formulation minimizes the blood level oscillations, dose related adverse effects and cost and ultimately improve the patient compliance and drug efficiency.
Keywords: Solvent evaporation technique, Bioavailability, Compatibility, Metacloperamide HCL etc.